An Analysis of Sport Employee Identification of NCAA Division I Compliance Employees - Melchert, Morgan; Downs, Benjamin; Walker, Khirey; Johnson, James (Journal of Amateur Sport, 2024)
The current study examined NCAA Division I compliance employees utilizing Sport Employee Identification (SEI; Oja et al., 2020). Little academic inquiry has focused on the various ways sport employees, like NCAA compliance employees, identify with their organization. The current study attempted to establish SEI as an applicable construct in sport scholarship and examine potential outcomes of SEI. Thus, the purpose of this study was to examine if SEI contributes to organizational behavior outcomes of job satisfaction, lower turnover intentions, and organizational citizenship behaviors with NCAA Division I compliance employees. The researchers utilized a demographic form and a 24-item survey including the SEI instrument, job satisfaction, turnover intentions, and the relationship between SEI and organizational citizenship behaviors. Data analysis consisted of confirmatory factor analysis, multiple one-way analysis of variance to analyze the connection between demographic variables and SEI, and regression analyses to examine the relationship between SEI and potential organizational behavior outcomes. A total of 217 responses highlighted job satisfaction and lower turnover intentions as outcomes of SEI, while organizational citizenship behaviors lacked enough support as an outcome of SEI. The findings have the potential to assist intercollegiate executives in better managing their compliance personnel and understanding compliance identification processes.